Pengaruh metode pengolahan terhadap senyawa antinutrisi biji asam jawa (Tamarindus indica) dan implikasinya bagi pakan ruminansia: kajian literatur - Veven Raymexen Bonat (Fakultas Pertanian Universitas Majalengka, 2025)
Tamarind (Tamarindus indica) seeds have potential as an alternative plant-based protein source for ruminant feed due to their high nutritional value. However, their utilization remains limited due to the presence of antinutritional compounds, such as tannins, phytic acid, saponins, and trypsin inhibitors, which reduce digestibility and nutrient availability. This literature review aims to analyze the effects of various processing methods on reducing antinutritional compounds in tamarind seeds and their implications for improving feed quality. The review encompasses five national and international studies that address biological (fermentation and germination) and physical–thermal (soaking, roasting, and steaming) treatments. Results indicate that fermentation is the most effective method for reducing phytic acid and trypsin inhibitors through microbial enzymatic activity, whereas soaking and roasting decrease tannin and saponin contents by more than 70%. Steaming and dry heating produce moderate reductions without compromising protein content. Combining biological and physical–thermal treatments yields the best results in lowering antinutritional compounds while enhancing digestibility and nutritional value. Therefore, tamarind seeds can serve as an economical and sustainable local protein source for ruminant feed formulation.